Novel protein acylations in ferroptosis: decoding the regulatory roles of lactylation, crotonylation, succinylation, and β-hydroxybutyrylation - Wei, Meiquan; Wei, Shiming; Xie, Xuhua; Liu, Taotao; Deng, Jun (Frontiers in Pharmacology, 2025)
Ferroptosis is a unique form of iron-dependent programmed cell death, characterized by the abnormal accumulation of lipid peroxides, which plays a important role in various physiological and pathological processes. Crucially, the activity and stability of core ferroptosis regulators (including GPX4, ACSL4, FSP1, and iron/lipid metabolism proteins) are dynamically controlled by diverse post-translational modifications (PTMs), positioning PTMs as central molecular switches modulating cellular ferroptotic susceptibility across pathophysiological contexts. Elucidating the regulatory mechanisms of PTMs in ferroptosis is of great significance for understanding the complex network of cell death and providing new perspectives for disease treatment and diagnosis. This review focuses on four emerging PTMs—lactylation, crotonylation, succinylation, and β-hydroxybutyrylation—and their roles in promoting ferroptosis progression via protein regulatory systems. Additionally, it explores their clinical potential as therapeutic targets and diagnostic biomarkers. The definitions, functional mechanisms, and enzymatic regulation of these PTMs are systematically elucidated.